Ecological studies: Biodiversity and ecosystem function - Ernst Detlef Schulze (Springer-Verlag, 1994)
This volume brings together in a substantive integrative manner the disciplines of population biology and ecosystem science, both directed toward evaluating the consequences of anthropogenic disruptions of natural systems